Genotype, extrapyramidal features, and severity of variant ataxia‐telangiectasia. Issue 2 (29th January 2019) - Schon, Katherine; van Os, Nienke J.H.; Oscroft, Nicholas; Baxendale, Helen; Scoffings, Daniel; Ray, Julian; Suri, Mohnish; Whitehouse, William P.; Mehta, Puja R.; Everett, Natasha; Bottolo, Leonardo; van de Warrenburg, Bart P.; et al.
Abstract : Objective: Variant ataxia‐telangiectasia is caused by mutations that allow some retained ataxia telangiectasia‐mutated (ATM) kinase activity. Here, we describe the clinical features of the largest established cohort of individuals with variant ataxia‐telangiectasia and explore genotype‐phenotype correlations. Methods: Cross‐sectional data were collected retrospectively. Patients were classified as variant ataxia‐telangiectasia based on retained ATM kinase activity. Results: The study includes 57 individuals. Mean age at assessment was 37.5 years. Most had their first symptoms by age 10 (81%). There was a diagnostic delay of more than 10 years in 68% and more than 20 years in one third of probands. Disease severity was mild in one third of patients, and 43% were still ambulant 20 years after disease onset. Only one third had predominant ataxia, and 18% had a pure extrapyramidal presentation. Individuals with extrapyramidal presentations had milder neurological disease severity. There were no significant respiratory or immunological complications, but 25% of individuals had a history of malignancy. Missense mutations were associated with milder neurological disease severity, but with a higher risk of malignancy, compared to leaky splice site mutations. Interpretation: Individuals with variant ataxia‐telangiectasia require malignancy surveillance and tailored management. However, our data suggest the condition may sometimes be mis‐ or underdiagnosed because of atypical features, including exclusive extrapyramidal symptoms, normal eye movements, and normal alpha‐fetoprotein levels in some individuals. Missense mutations are associated with milder neurological presentations, but a particularly high malignancy risk, and it is important for clinicians to be aware of these phenotypes.ANN NEUROL 2019;85:170–180.